S1 guidelines on the diagnosis and treatment of scabies – short version. (23rd November 2016) - Sunderkötter, Cord; Feldmeier, Hermann; Fölster‐Holst, Regina; Geisel, Bertram; Klinke‐Rehbein, Sabine; Nast, Alexander; Philipp, Sandra; Sachs, Bernhardt; Stingl, Julia; Stoevesandt, Johanna; Hamm, Henning
Summary: The goals of this German guideline are the improvement of diagnosis and therapy of scabies, the implementation of a coordinated action in outbreaks of scabies, and the control of this infestation in large migration or refugee flows. Sarcoptes scabiei var. hominis is transmitted by direct skin‐to‐skin contact of sufficient duration. The infectivity of female mites when removed from patients does not exceed 48 hours at room temperature (21°C) and relative humidity of 40‐80%. The risk of infection rises proportionally to the number of mites on the skin and is particularly high in crusted scabies. As elderly persons tend to develop crusted scabies due to disease‐ or medication‐related immunosuppression, there is an increased risk for outbreaks of scabies at nursing homes and extended‐care facilities. The guideline contains detailed recommendations for management of such outbreaks. In refugees the prevalence of scabies is higher than in the general population in Germany, but the risk for outbreaks is not high. Scabies infestation should be considered when a recent onset of itching is associated with eczema and presence of burrows or comma‐like papules at predilection sites. It is confirmed by dermatoscopic detection of mites or by microscopic identification of mites, mite eggs or fecal matter (scybala) from skin scrapings.The treatment of choice for common scabies is topical permethrin 5% cream applied for 8‐12 hours. Permethrin can be considered for off‐label use also in infants of less than 3 months of age and pregnant women. For this group crotamiton is another option, which, besides benzyl benzoate, presents a good second line therapy for the other indications. Indications for oral ivermectin, which has just been licensed in Germany, include patients with immunosuppression, severe dermatitis, and low adherence.Crusted scabies is preferentially treated by a combination of topical permethrin and oral ivermectin. Affected patients should be isolated, and all contact persons should be treated. The guideline contains lists for additional measures, including possible treatment of contact persons, clothes, linen and other possibly infested articles.